Significance of histology in determining management of lesions regrowing after radiosurgery - Nath, Sameer; Sheridan, Alison D.; Rauch, Philipp; Yu, James B.; Minja, Frank J.; Vortmeyer, Alexander O.; Chiang, Veronica L. (Journal of neuro-oncology, 2014)
Brain metastases treated with stereotactic radiosurgery may show delayed enlargement on post-treatment imaging that is of ambiguous etiology. Histopathologic interpretation of brain specimens is often challenging due to the presence of significant radiation effects admixed with irradiated residual tumor of indeterminate viability. The purpose of this study was to assess the impact of histologic findings on clinical outcomes following resection of these lesions.
Gesehen am 25.08.2020